2016
DOI: 10.1097/dbp.0000000000000308
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Deficit/Hyperactivity Disorder–Related Impulsivity and Cyberbullying in Social Media

Abstract: Sarah is a 13-year-old eighth grader who was recently diagnosed for the first time with attention-deficit/hyperactivity disorder (ADHD)-inattentive type, and the family elected to treat her with behavioral interventions to help her organization and attention. She had struggled with distractibility and disorganization since the fourth grade. At home, Sarah's mother described her as "spacey" and unable to complete the morning routine without constant supervision. Over time, her mother observed that it seemed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Moreover, Heiman, Shemesh, and Eden (2015) reported that students with ADHD feel greater social loneliness via the Internet. Reilly, Fogler, Selkie, and Augustyn (2016) conducted a study on a girl with ADHD who encountered cyberbullying because of posting photographs of herself in various stages of undress on Snapchat, which resulted in significant family problems.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Heiman, Shemesh, and Eden (2015) reported that students with ADHD feel greater social loneliness via the Internet. Reilly, Fogler, Selkie, and Augustyn (2016) conducted a study on a girl with ADHD who encountered cyberbullying because of posting photographs of herself in various stages of undress on Snapchat, which resulted in significant family problems.…”
Section: Introductionmentioning
confidence: 99%
“…Other disability studies differentiate diagnostic subgroups of cognitive disabilities in their research (cf. Section 1.3), for example, research and design with individuals with autism (Alcorn et al, 2011;Burke et al, 2010;Gwynette et al, 2018;Harrington et al, 2014;Iglesias et al, 2019;Pinchevski and Peters, 2016;Ringland et al, 2016;Spiel et al, 2017) or ADHD (Becker and Lienesch, 2018;Reilly et al, 2016;Sonne et al, 2016), or down syndrome (Feng et al, 2008). We take inspiration from these studies in the data collection and the interpretation of our empirical findings.…”
Section: Defectologymentioning
confidence: 99%
“…Another supportive, as opposed to protective, initiative addressed in Paper 3 and the literature is 'parental mediation technology'. Here, parents set the rules and guidelines for Internet use while maintaining an open dialogue with their children about such matters (Reilly et al, 2016;Wright, 2017aWright, , 2017b, providing them with at least some independence over their digital lives. In addition, there is potential for mutual learning when using this approach: the children can learn from their parents, and the parents can learn from what their children share about their digital lives.…”
Section: Support Vs Protectionmentioning
confidence: 99%